CORE COMPETENCIES OF LOCAL GOVERNMENT IN STRATEGIC PLANNING (A STUDY ON LEBAK REGENCY, BANTEN PROVINCE) - Rusito; Jumanah (Sawala : Jurnal Administrasi Negara, 2026)
This study analyzes the core competence of local government in strategic planning, particularly the integration of institutional capacity, policy innovation, human resource development, and digital governance within the Regional Medium-Term Development Plan (RPJMD) of Lebak Regency for 2025–2029. The theoretical reference is based on Hamel and Prahalad (1990), who identify three main dimensions of core competence: the ability to provide access to a wide variety of markets, significant contribution to perceived value or benefits, and competencies that are difficult for competitors to imitate. This research employs a descriptive qualitative approach through document analysis using the interactive analysis model of Miles, Huberman, and Saldaña (2019). The findings indicate that local government core competence plays an important role in expanding cross-sector development access, improving public service quality and community satisfaction, and strengthening regional competitiveness based on local potential. Strengthening these core competencies is therefore a strategic factor in supporting sustainable regional development and achieving Indonesia’s Golden Vision 2045.